(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This research explores the integration of digital diplomacy and inclusive education, focusing on the role of modern technologies, such as artificial intelligence and algorithm-based systems, in enhancing global communication and educational opportunities. Digital diplomacy has become an essential tool for states to improve international relations, while digital education platforms offer solutions to address inequalities in access to quality education. The study examines the challenges and opportunities presented by these technological advancements, including issues of cybersecurity, data privacy, and infrastructure gaps in developing countries. By analyzing various case studies and literature, the research highlights the mutual benefits of combining digital diplomacy with inclusive education to foster more equitable international cooperation and improve access to education worldwide. The findings suggest that while there are significant opportunities for digital transformation, overcoming existing barriers is essential for maximizing the effectiveness of these technologies.